Widespread and dynamic expression of granzyme C by skin-resident antiviral T cells - Lujan, Ramon A.; Pei, Luxin; Shannon, John P.; Dábilla, Nathânia; Dolan, Patrick T.; Hickman, Heather D. (Frontiers in Immunology, 2023)
After recognition of cognate antigen (Ag), effector CD8+ T cells secrete serine proteases called granzymes in conjunction with perforin, allowing granzymes to enter and kill target cells. While the roles for some granzymes during antiviral immune responses are well characterized, the function of others, such as granzyme C and its human ortholog granzyme H, is still unclear. Granzyme C is constitutively expressed by mature, cytolytic innate lymphoid 1 cells (ILC1s). Whether other antiviral effector cells also produce granzyme C and whether it is continually expressed or responsive to the environment is unknown. To explore this, we analyzed granzyme C expression in different murine skin-resident antiviral lymphocytes. At steady-state, dendritic epidermal T cells (DETCs) expressed granzyme C while dermal γδ T cells did not. CD8+ tissue-resident memory T cells (TRM) generated in response to cutaneous viral infection with the poxvirus vaccinia virus (VACV) also expressed granzyme C. Both DETCs and virus-specific CD8+ TRM upregulated granzyme C upon local VACV infection. Continual Ag exposure was not required for maintained TRM expression of granzyme C, although re-encounter with cognate Ag boosted expression. Additionally, IL-15 treatment increased granzyme C expression in both DETCs and TRM. Together, our data demonstrate that granzyme C is widely expressed by antiviral T cells in the skin and that expression is responsive to both environmental stimuli and TCR engagement. These data suggest that granzyme C may have functions other than killing in tissue-resident lymphocytes.